Core–shell assembly of carbon nanofibers and a 2D conductive metal–organic framework as a flexible free-standing membrane for high-performance supercapacitors. Issue 7 (4th June 2019) - Zhao, Shihang; Wu, Huihui; Li, Yanli; Li, Qin; Zhou, Jiaojiao; Yu, Xianbo; Chen, Hongmei; Tao, Kai; Han, Lei
Abstract : A hybrid core–shell material based on carbon nanofibers and a 2D conductive metal–organic framework has been fabricated into a flexible free-standing membrane as an electrode material for supercapacitors. Abstract : A hybrid core–shell material based on carbon nanofibers (CNFs) and a 2D conductive metal–organic framework (Ni-CAT) has been synthesized as a flexible free-standing membrane by combining electrospinning technology with a hydrothermal method. The as-made CNF@Ni-CAT exhibits a high specific capacitance of 502.95 F g −1 at a current density of 0.5 A g −1 and an improved cycling stability of 73% capacitance retention over 5000 cycles as an electrode material for supercapacitors due to its excellent synergistic effect. Furthermore, the asymmetric supercapacitor assembled from CNF@Ni-CAT and AC shows a high energy density of 18.67 W h kg −1 at a power density of 297.12 W kg −1 and maintains 106.19% of the original specific capacitance after 5000 cycles. This simple synthesis strategy of combining electrospinning technology with a hydrothermal method can not only solve the agglomeration problem of 2D conductive MOFs, but also improve the electrochemical properties of carbon nanofiber-based materials, and the flexible composite membrane provides a new direction for the research on flexible supercapacitors.